Regulatory mechanisms controlling biogenesis of ubiquitin and the proteasome - London, MK (2018)
Analysis of several Saccharomyces cerevisiae ump mutants with defects in ubiquitin (Ub)-mediated proteolysis yielded insights into the regulation of the polyubiquitin gene UB14 and of proteasome genes. High-molecular weight Ub-protein conjugates accumulated in ump mutants with impaired proteasome function with a concomitant decrease in the amount of free Ub. In these mutants, transcriptional induction of UB14 was depending in part on the transcription factor Rpn4. Deletion of UB14 partially suppressed the growth defects of ump1 mutants, indicating that accumulation of polyubiquitylated proteins is deleterious to cell growth. Transcription of proteasome subunit genes was induced in ump mutants affecting the proteasome, as well as under conditions that mediate DNA damage or the formation of abnormal proteins. This induction required the transcriptional activator Rpn4. Elevated Rpn4 levels in proteasome-deficient mutants or as a response to abnormal proteins were due to increased metabolic stability. Up-regulation of proteasome genes in response to DNA damage, in contrast, is shown to operate via induction of RPN4 transcription. (C) 2004 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.